2006
DOI: 10.1194/jlr.m500444-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic SR-BI-mediated cholesteryl ester selective uptake occurs with unaltered efficiency in the absence of cellular energy

Abstract: Scavenger receptor class B type I (SR-BI) plays a critical role in the delivery of HDL cholesterol and cholesteryl esters (CEs) to liver and steroidogenic tissues by a selective process that does not result in significant degradation of HDL protein. Recently, SR-BI-mediated endocytosis and recycling of HDL have been demonstrated. However, it remains unclear whether efficient SR-BI-mediated selective uptake occurs strictly at the plasma membrane or at additional sites along its endocytic itinerary. To examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
1
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 39 publications
4
34
1
2
Order By: Relevance
“…Although some in vitro studies showed that SR-BI-mediated selective uptake does not require endocytosis 30,31 and SR-BI is able to mediate selective uptake into phospholipid vesicles in the absence of a cellular environment, 32 other data suggested that SR-BI is an endocytic receptor. 33 Vesicular trafficking of SR-BI together with HDL through the early endosome system to subapical compartments, where cholesteryl ester hydrolysis likely takes place, has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Although some in vitro studies showed that SR-BI-mediated selective uptake does not require endocytosis 30,31 and SR-BI is able to mediate selective uptake into phospholipid vesicles in the absence of a cellular environment, 32 other data suggested that SR-BI is an endocytic receptor. 33 Vesicular trafficking of SR-BI together with HDL through the early endosome system to subapical compartments, where cholesteryl ester hydrolysis likely takes place, has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is established that SR-BI can effectively mediate selective uptake without the concomitant internalization of the HDL particle, there is evidence that a fraction of HDL is internalized together with SR-BI (13,14,16). The functional significance of HDL internalization is not understood.…”
Section: Sr-bi Trafficking Through Late Endosomes/lysosomes Is Rab7 Dmentioning
confidence: 99%
“…Cells were cultured in DMEM supplemented with 10% (v/v) fetal calf serum, 100 U/ml penicillin, 100 mg/ml streptomycin, and 2 mM L-glutamine. Primary hepatocytes were isolated from retired breeders of the C57BL6 (wild-type) mouse strain purchased from Charles River (Wilmington, MA) and SR-BI 2/2 mice (18) as previously described (16). Other reagents and suppliers included: filipin (Sigma Mississauga, ON, Canada), human plasma HDL (Calbiochem, San Diego, CA), anti-LAMP-2 and anti-EEA1 Abs (Transduction Laboratories, Mississauga, ON, Canada), anti-SR-BI Ab (NB400-101) (Novus Biologicals, Little-ton, CO), anti-Rab7 Ab (Sigma), and Lipofectamine 2000 (Invitrogen, Burlington, ON, Canada).…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Other studies, however, have provided strong evidence that selective lipid uptake does not depend on HDL internalization by SR-BI and that the bulk of selective lipid uptake occurs at the plasma membrane. 11,12 The importance of SR-BI in the regulation of HDL levels, as well as in biliary cholesterol secretion, has been well demonstrated in studies of SR-BI genetically altered mice. 3,13 In addition to functioning in the liver as an HDL receptor, SR-BI also contributes to the metabolism of chylomicron remnants.…”
mentioning
confidence: 99%